37th [IARCS] Annual Conference on Foundations of Software Technology and Theoretical Computer Science, [FSTTCS] 2017, December 11-15, 2017, Kanpur, India - Lokam, Satya; Ramanujam, R. (Schloss Dagstuhl - Leibniz-Zentrum f[\"[u]]r Informatik, 2018)
37th [IARCS] Annual Conference on Foundations of Software Technology and Theoretical Computer Science, [FSTTCS] 2017, December 11-15, 2017, Kanpur, India